2009
DOI: 10.1197/jamia.m2956
|View full text |Cite
|
Sign up to set email alerts
|

The Adequacy of ICNP Version 1.0 as a Representational Model for Electronic Nursing Assessment Documentation

Abstract: A b s t r a c t Objectives:The purpose of this study was to evaluate the adequacy of the International Classification of Nursing Practice 1 (ICPN) Version 1.0 as a representational model for nursing assessment documentation. Design and Measurements:To identify representational requirements of nursing assessments, the authors mapped key concepts and semantic relations extracted from standardized and local nursing admission assessment documentation forms/templates and inpatient admission assessment records to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…Along these lines, many studies have compared different systems and identified criteria to assess and validate terminologies [21,24,36]. Similar studies illustrate that not all criteria are met [22,[37][38][39] and support the earlier study conducted by Bakken et al [22], which found that none of the existing systems met all the criteria for complete, comprehensive, clear, and non-redundant representations of concepts. We acknowledge these findings, but rather than see this as a shortcoming of a terminology system, we see this as more or less a general characteristic as it is not possible to develop a system that fits all aspects of nursing care.…”
Section: Background and Status On Standardization In Nursingsupporting
confidence: 62%
“…Along these lines, many studies have compared different systems and identified criteria to assess and validate terminologies [21,24,36]. Similar studies illustrate that not all criteria are met [22,[37][38][39] and support the earlier study conducted by Bakken et al [22], which found that none of the existing systems met all the criteria for complete, comprehensive, clear, and non-redundant representations of concepts. We acknowledge these findings, but rather than see this as a shortcoming of a terminology system, we see this as more or less a general characteristic as it is not possible to develop a system that fits all aspects of nursing care.…”
Section: Background and Status On Standardization In Nursingsupporting
confidence: 62%
“…There have been research studies conducted across cross-cultures using ICNP. These include cross mapping studies, validation studies and computer data base analysis (Dykes et al, 2009). …”
Section: International Classifi Cation Of Nursing Practicementioning
confidence: 99%
“…Currently, several classification systems are compatible with computer systems that describe nursing care, including the International Classification for Nursing Practice (ICNP®) (3) . Because this system is a multiaxial classification of terms represented in a seven-axis model (i.e., Focus, Judgment, Means, Time, Location, Client, and Action), it allows for combining the terms belonging to the axes and for composing titles called Nursing Diagnoses (ND), Interventions, and Outcomes.…”
Section: Descriptoresmentioning
confidence: 99%